Fundamentalidade do direito à saúde e sua efetivação sob a ótica da hodierna Constituição - Fuchs, Horst Vilmar (2007)
Brazilian constitution assures people access to health care systems, taking them as a fundamental service, granted by the State. Nevertheless, omissions by Executive Power and, in consequence, demanding the Judicial Power to obtain access to treatments and, primary, very expensive medicines; it has guaranteed the guardianship for the patients who can not effort the therapy. The State has a deficient and insufficient structure to take care of to the demands, alleging lack of resources; this movement provokes a search for private systems of services to the health. This picture leads to the analysis of the environment of private health care organizations and its pertinent legislation, also demands studies of the existing budgetary systems in our legal system. We verify the legislative treatment for which they pass the budgets and the level of accompaniment of the society. Circumstances above had led to analysis of origin of State and its purpose, making one brief boarding of its evolution, until to arrive at our days, where we find a constitution that draws a State under a social vocation, but offers a precarious structure. Under the form as if it organizes and it chooses priorities, we analyze the Liberal State and the Social State; the division of the attributions of the State created the base for, more ahead, to consider the paper of each one to bring those rights for a real life. A sounding, even so superficial, in the legal and physical systems of health in Portugal and the countries of the Cooperation for Economic Development Organization, also revealed opportune, bringing essential lessons to establish a paradigm for the Brazilian system of health. One concludes that the health politics involve and demand a reevaluation of the budgetary process, build a stronger structure of health care systems with better hospitals, clinics and professionals. However, the health politics must be more including: they involve all even though the practical structure of the State, reaching the economic policies and of basic and basic education. Concerning to the reach of the health politics, does not have in the legal system an objective basis for expenses with patients in therapies and medicines, compelling to look at a legally acceptable method it Executive to know as to act ahead of the demand that patient makes to it, searching in the Brazilian Civil Code, arriving at the equation capacity/necessity. We verify, finally, that the health system understands all the actions of all the Ministries; it involves, by the way, all the attributions of the State. Health is the main one of the basic rights, therefore human being connects itself directly to the dignity of the life.